Circular RNA circβ‐catenin aggravates the malignant phenotype of non‐small‐cell lung cancer via encoding a peptide. Issue 9 (23rd July 2021) - Zhao, Weijun; Zhang, Yandan; Zhu, Yonggang
Abstract: Background: More and more evidences demonstrate that circular RNAs (circNRAs) can encode protein. As a circRNA with translation capabilities, outcomes of circβ‐catenin in non‐small cell lung cancer (NSCLC) still need to be explored. Method: The research methods of circβ‐catenin in the article include qRT‐PCR, wound healing assay, CCK‐8, colony formation, and Transwell assay. Western blotting and immunofluorescence were provided to detect protein expression levels and peptide encoded by circβ‐catenin, respectively. Results: A prominently higher circβ‐catenin expression was found in NSCLC tissues. Silencing of circβ‐catenin was able to inhibit NSCLC cell migrating, invasive, and proliferative phenotypes. Overexpression of circβ‐catenin could enhance the migrating, invasive, and proliferative phenotypes of NSCLC cells. Importantly, circβ‐catenin was found to encode a peptide in NSCLC cells. Silencing or overexpression of circβ‐catenin could reduce or increase β‐catenin protein expression via suppressing the degradation of β‐catenin. Conclusion: Circβ‐catenin could promote NSCLC cell malignant phenotypes via peptide‐regulated β‐catenin pathway. Our study provided a new understanding for the mechanisms of NSCLC. Abstract : β‐catenin‐370aa encoded by circβ‐catenin may act as a decoy for GSK3β to sponge with GSK3β, leading to escape the degradation of β‐catenin induced by GSK3β.